1996
DOI: 10.1093/fampra/13.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A troubled youth: Relations with somatization, depression and anxiety in adulthood

Abstract: The high prevalence of triple problems suggests a need to reconsider concepts like somatic anxiety and anxious depression. The specificity of the relation between deprivation and somatization and of the relation between other life events and depression indicates that distinct causal mechanisms (in youth) contribute to these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
1
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 31 publications
3
30
1
2
Order By: Relevance
“…One potential mechanism is that maltreatment conditions the child to respond to stress by increasing food intake and/or decreasing activity (Greeno & Wing, 1994;Steptoe, Wardle, Pollard, Canaan, & Davies, 1996). Childhood maltreatment is a well-established risk factor for later depression and anxiety (Mullen, Martin, Anderson, Romans, & Herbison, 1996; OakleyBrowne, Joyce, Wells, Bushnell, & Hornblow, 1995; Portegijs, Jeuken, van der Horst, Kraan, & Knottnerus, 1996), and several studies have now shown that symptoms of depression and anxiety in childhood are associated with the later development of obesity, particularly in females (Anderson, Cohen, Naumova, & Must, 2006;Goodman & Whitaker, 2002;Hasler et al, 2005;Pine, Goldstein, Wolk, & Weissman, 2001;Richardson et al, 2003). Depression and/ or anxiety resulting from maltreatment may be associated with neuro-endocrine responses that alter metabolism, activity levels, or appetite (Bjorntorp, 2001;Chrousos, 2000;Nemeroff, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…One potential mechanism is that maltreatment conditions the child to respond to stress by increasing food intake and/or decreasing activity (Greeno & Wing, 1994;Steptoe, Wardle, Pollard, Canaan, & Davies, 1996). Childhood maltreatment is a well-established risk factor for later depression and anxiety (Mullen, Martin, Anderson, Romans, & Herbison, 1996; OakleyBrowne, Joyce, Wells, Bushnell, & Hornblow, 1995; Portegijs, Jeuken, van der Horst, Kraan, & Knottnerus, 1996), and several studies have now shown that symptoms of depression and anxiety in childhood are associated with the later development of obesity, particularly in females (Anderson, Cohen, Naumova, & Must, 2006;Goodman & Whitaker, 2002;Hasler et al, 2005;Pine, Goldstein, Wolk, & Weissman, 2001;Richardson et al, 2003). Depression and/ or anxiety resulting from maltreatment may be associated with neuro-endocrine responses that alter metabolism, activity levels, or appetite (Bjorntorp, 2001;Chrousos, 2000;Nemeroff, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The multiplicity of complaints and symptoms reported during our interviews, however, suggests a high degree of medicalization 35 by patients and family doctors, which is in agreement with the fi nding that patients who consult frequently have a much higher rate (40% to 50%) of physical disease than does the average attender. 17,18 The apparent inability of these patients to accommodate physical sensations or symptoms and to consistently seek out medical advice (despite such obstacles as reception staff and practice systems) suggests several possibilities. Their physical feedback mechanisms may be amplifi ed, leading to a heightened experience of their bodies and an inability to distinguish between normal and abnormal sensations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they are reported to be more likely to suffer with psychological and psychiatric problems, such as somatization, to have higher rates of physical disease, and to have poorer health beliefs when compared with those who are not frequent attenders. [16][17][18][19][20] Despite their heterogeneity, FREQUENT ATTENDERS there have been attempts to identify subgroups, such as Katon' s "distressed high utilizers," 16 and Karlsson' s 5 patient groups: patients with entirely physical illness, patients with clear psychiatric illnesses, crisis patients, chronically somatizing patients, and patients with multiple problems. 21 We decided to approach frequent attendance from another perspective, that is, what do patients themselves think about consulting a family doctor?…”
Section: Introductionmentioning
confidence: 99%
“…Somatisation in general practice was found to be associated with damaging earlier life events, often unknown to the general practitioner [21,22]. Mollica [23] advocates the systematic assessment of the impact of traumatic life experiences in new primary care patients, especially refugees.…”
Section: Introductionmentioning
confidence: 99%